Rehabilitation As a Penal Policy for Online Gambling Offenders in Indonesia: A Normative Legal Analysis - Sri Setiawati; Rizki Adi Pinandito (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Rapid technological advancement has transformed social and economic life by expanding global connectivity and access to information, yet it has also enabled cyber-enabled offending, including online gambling, which operates with heightened anonymity and scalability. In Indonesia, these characteristics generate persistent enforcement challenges and significant social harms that require responses beyond conventional punitive paradigms. This study aims (i) to examine and analyse the implementation of criminal sanctions for online gambling offenders in Indonesia, and (ii) to assess whether rehabilitation can be applied as a penal measure for such offenders. The research employs a normative juridical method grounded in positive law, using a descriptive–analytical approach to systematise relevant legal instruments and derive policy-oriented implications. The study finds that, although online gambling has been prosecuted through the KUHP and supplemented by sectoral instruments, enforcement has historically been constrained by doctrinal fragmentation and limited deterrent effect, resulting in relatively nominal sanctions and short custodial outcomes in practice. It further concludes that the synchronisation of the New KUHP (Law No. 1 of 2023) and the Second Amendment to the UU ITE (Law No. 1 of 2024) strengthens the sanctioning architecture through technology-specific criminalisation and economically meaningful penalties, while rehabilitation remains a necessary complementary measure to address the underlying psychological and social vulnerabilities that sustain demand and recidivism.